A case report of blunt intraoral cerebrovascular injury in a child following intraoral trauma: The pen is mightier than the sword. (February 2022) - Hon, Kay; Roach, Denise; Dawson, Joseph
Abstract: Carotid artery dissection in the paediatric population is uncommon and in rare cases it can be due to intraoral blunt trauma associated with a stick-like object such as pen or chopstick in the mouth at the time of injury. Given the rarity of the condition, there is significant knowledge gap in evidence-based diagnosis and management of paediatric blunt cerebrovascular injury (BCVI). This case report presents a rare case of asymptomatic carotid artery dissection due to intraoral blunt trauma in a young patient and the successful conservative management. This report also demonstrated the sonographic progression of the carotid artery dissection on follow up imaging.